A New Approach to Minimise Network Blocking In 4g for Better Accessibility (International Journal of Engineering and Computer Science, 2013)
Mobile communications systems revolutionized the way people communicate, joining together communications and mobility. Along way in a remarkably short time has been achieved in the history of wireless. Evolution of wireless access technologies is about to reach its fourth generation (4G).The first generation (1G) has fulfilled the basic mobile voice, while the second generation (2G) has introduced capacity and coverage. This is followed by the third generation (3G), which has quest for data at higher speeds to open the gates for truly “mobile broadband” experience, which will be further realized by the fourth generation (4G).The Fourth generation (4G) will provide access to wide range of telecommunication services, including advanced mobile services, supported by mobile and fixed networks. In today’s Internet these applications are not subject to blocking, therefore the growth of popularity of these applications may endanger the stability of the Internet. In this paper, we propose a novel model to have more accessibility to network through duplication strategy.